Penerapan Algoritma Decision Tree dalam Menentukan Kelayakan Penerima Bantuan Program Keluarga Harapan - Mandala, Eka Praja Wiyata; Putri, Dewi Eka (STMIK Banjarbaru, 2026)
Determining the eligibility of beneficiaries for the Family Hope Program still faces targeting inaccuracies due to limited data analysis and subjective decision-making. This study aims to develop a Decision Tree–based classification model to objectively determine Family Hope Program eligibility using data-driven approaches. The dataset includes socio-economic attributes such as income, DTKS status, school-age children, pregnant or breastfeeding mothers, elderly members, disabilities, and occupation. The data were processed through cleaning, transformation, and splitting into training and testing sets. Experimental results show that the model achieved a highest accuracy of 96.00%, along with high precision and recall values. The resulting decision tree structure also provides interpretable rules to support decision-making. These findings demonstrate that the Decision Tree method is effective in improving the accuracy and transparency of Family Hope Program beneficiary selection.Keywords: Decision Tree; Family Hope Program; Classification; Data Mining; Social Assistance AbstrakPenentuan kelayakan penerima Program Keluarga Harapan masih menghadapi permasalahan ketidaktepatan sasaran akibat keterbatasan analisis data dan subjektivitas dalam pengambilan keputusan. Penelitian ini bertujuan mengembangkan model klasifikasi berbasis Decision Tree untuk menentukan kelayakan penerima Program Keluarga Harapan secara objektif dan berbasis data. Dataset yang digunakan mencakup atribut sosial ekonomi seperti pendapatan, status DTKS, usia sekolah, ibu hamil atau menyusui, lansia, disabilitas, dan pekerjaan. Data diproses melalui tahap pembersihan, transformasi, dan pembagian data latih dan uji. Hasil pengujian menunjukkan bahwa model mencapai akurasi tertinggi sebesar 96,00%, dengan presisi dan recall yang tinggi. Struktur pohon keputusan juga menghasilkan aturan yang mudah diinterpretasikan sebagai dasar pengambilan keputusan. Hasil ini membuktikan bahwa Decision Tree efektif untuk meningkatkan ketepatan dan transparansi penyaluran bantuan Program Keluarga Harapan.Kata kunci: Decision Tree; Program Keluarga Harapan; Klasifikasi; Data Mining; Bantuan Sosial